A Laboratory Investigation of the Effect of Temperature on Densities and Viscosities of Unconventional Fuel (RFO) and Petroleum Diesel Oil - Maduka Augustine Nwufo; Iwenofu Chinwenwa Onyedika; Jisieike Chiazor Faustina (Universitas Negeri Surabaya or The State University of Surabaya, 2026)
Understanding the thermal behavior of fuels is critical for optimizing engine performance, combustion efficiency and emissions control. This study investigates the effect of temperature on the viscosity and density of Residual Fuel Oil (RFO) - an unconventional heavy fuel and standard diesel oil. Laboratory experiments were conducted from 20°C to 100°C at 10°C intervals. Viscosity and density measurements were taken using a digital rotational viscometer and a hydrometer respectively, following ASTM D445 and D1298 standards. Results revealed that RFO exhibited a high initial viscosity of 210.5 cSt at 20°C, which significantly decreased to 20.6 cSt at 100°C, indicating a 90.2% reduction. In contrast, diesel maintained a more stable profile, dropping from 3.52 cSt to 1.18 cSt over the same range. Density also declined with temperature, from 1012.30 kg/m³ to 904.70 kg/m³ for RFO, and 850.6 kg/m³ to 777.30 kg/m³ for diesel. Regression analysis yielded strong exponential fit models with R² values of 0.989 and 0.978 for RFO and diesel viscosity, respectively, confirming predictable thermal behavior. These findings suggest that preheating RFO to at least 80°C is necessary to achieve viscosity levels ( 38.2 cSt) suitable for efficient atomization and combustion in existing diesel engines. The study provides empirical evidence supporting the feasibility of RFO as a partial diesel substitute when thermally conditioned, and it highlights the need for thermal compensation in volume-based fuel metering systems.